Experimental evaluation of fracture stabilizers - Jingchen ZHANG; Shicheng ZHANG; Xiaobing BIAN; Zhaofeng ZHUANG; Tiankui GUO (Petroleum Exploration and Development, 2013)
To avoid the closure of once created fractures in unconsolidated sandstone reservoirs after fracturing, an optimum fracture stabilizer was selected through experimental evaluation, dosage optimization and analysis of its suitability with other commonly used fracturing fluids. A modified resin was selected as the fracture stabilizer, which can form an adhesive film with certain adhesion intensity on the surface of the proppant to fill fractures despite the slightly decreased conductivity. The conductivity, sand control effect, suitability with guanidine gum and viscoelastic surfactant fracturing fluids (VES) of fracture stabilizers with different ratios were evaluated in the experiment. The dosage of the fracture stabilizer was optimized according to conductivity results and sand control effect. After a comprehensive evaluation, fracture stabilizer of 3% to 5% mass fraction is recommended to be used with the guanidine gum fracturing fluid. The simulation experiments show that the flow conductivity of fractures could be maintained by fracture stabilizers and in the proppant processed by stabilizers the number of intrusive particles was significantly reduced. Key words: fracture stabilizer, conductivity, sand control effect, fracturing fluid